Implementation of risk management process at KPMJ Khidmat Sdn Bhd / Che Noraini Che Zamani - Che Zamani, Che Noraini (Faculty of Business and Management, 2010)
The subject matter of this project paper is on the “Implementation of Risk Management Process At KPMJ Khidmat Sdn Bhd”. It consist an introduction, which relates to the background and/or history of the parent company, namely Koperasi Permodalan Melayu Negeri Johor (KPMNJ), as well as on KPMJ Khidmat Sdn Bhd, as a subsidiary of KPMNJ, the services and products offered by KPMJ Khidmat Sdn Bhd, and the process of risk management. The study will focus on the practice of risk management process by KPMJ Khidmat of KPMNJ.